Penerapan Metode Microlearning untuk Meningkatkan Literasi Membaca Siswa Sekolah Dasar - Dewi Lestari; Riyan Pratama; Nabila Safitri (Gema Cendekia Institute, 2026)
This study aims to analyze the effectiveness of implementing the microlearning method in improving reading literacy in elementary school students. Reading literacy is a fundamental skill that is crucial for students because it serves as the foundation for understanding learning materials in various subjects. However, many elementary school students still experience difficulties in comprehending reading texts, mastering vocabulary, and determining main ideas and conclusions. This study used a quantitative approach with a quasi-experimental design using a one-group pretest-posttest design. The subjects were elementary school students selected using a purposive sampling technique. Data collection was conducted through reading literacy tests (pretest and posttest), observations of student activities during learning, and questionnaires assessing student responses to the microlearning implementation. The microlearning treatment was implemented through short lessons lasting 10–15 minutes each session using micro-content in the form of short texts, short videos, vocabulary exercises, and quick quizzes. The results showed an increase in students' reading literacy skills after the microlearning implementation, as evidenced by an increase in posttest scores compared to pretest scores. Furthermore, observations indicated that students were more active, focused, and enthusiastic in participating in the learning process. Student response questionnaires also indicated that microlearning was perceived as more engaging and facilitated reading comprehension. Thus, microlearning has been proven effective in improving elementary school students' reading literacy and can be an alternative, innovative, technology-based learning strategy relevant for implementation in the digital age.